Mit dem letzten Zug nach England : Opposition, Exil, Heimkehr - Zadek, Alice 1921-; Zadek, Gerhard, 1919- 1919- (Dietz, 1992)
German Jews born and educated in Berlin describe their flight to England in 1939, eventual return to East Germany (1947), and then back to Berlinand West Germany.